Penerapan Micro Teaching Sebagai Strategi Inovatif Dalam Meningkatkan Kualitas Pengajaran Pada Pendidikan Islam Anak Usia Dini - Fauziah Nasution; Septi Ayu Harahap; Masdeani Dasopang; Dini Rosmana Tanjung; Zulham Efendi Marpaung (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2024)
One of the innovative strategies that has been proven effective in improving the quality of teaching is the Micro Teaching method. This method involves teaching simulations on a small scale with a focus on the important components of learning. This article aims to explain the application of Micro Teaching as an innovative strategy in improving the quality of teaching in early childhood Islamic education. This article outlines the basic principles of Micro Teaching and how their application can make a positive contribution to teaching in the context of early childhood Islamic education. The research used a descriptive-analytical approach with literature analysis. This research is qualitative in nature, where we did not collect primary data through surveys or interviews. the application of Micro Teaching as an innovative strategy in early childhood Islamic education has great potential to improve teaching quality, religious understanding, and the holistic development of Muslim children. With commitment and good cooperation from all related parties, it is hoped that the application of Micro Teaching can have a positive and sustainable impact on early childhood Islamic education.